1999
DOI: 10.1097/00000542-199907000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Contractility in Humans after Coronary Artery Surgery 

Abstract: The current results strongly suggest that propofol lacks direct cardiac depressant effects. Nevertheless, meaningful vascular actions of propofol could be demonstrated. Significant decreases in ventricular loading conditions accounted for a marked decrease in arterial blood pressure and supported the concept that propofol in clinically relevant concentration is a vasodilator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 44 publications
1
27
0
2
Order By: Relevance
“…We got similar results in our study with significant decrease in arterial blood pressure, after induction with propofol which did not increase above baseline value after intubation, while, with etomidate, there was significant increase in arterial pressure following intubation. Also, increase in heart rate occurred with all agents after laryngoscopy and intubation Schmidt et al [21] found in their study that, hypotension caused by propofol is due to the reduction of heart's preload and afterload, which are not synchronized with heart's compensatory responses such as increased cardiac output and increased HR. This hemodynamic drop would be intensified by high doses of the drug and high speed injection of the drug.…”
Section: Citationmentioning
confidence: 92%
“…We got similar results in our study with significant decrease in arterial blood pressure, after induction with propofol which did not increase above baseline value after intubation, while, with etomidate, there was significant increase in arterial pressure following intubation. Also, increase in heart rate occurred with all agents after laryngoscopy and intubation Schmidt et al [21] found in their study that, hypotension caused by propofol is due to the reduction of heart's preload and afterload, which are not synchronized with heart's compensatory responses such as increased cardiac output and increased HR. This hemodynamic drop would be intensified by high doses of the drug and high speed injection of the drug.…”
Section: Citationmentioning
confidence: 92%
“…We further determined heart rate (bpm), mean arterial blood pressure (mm Hg), cardiac output (L/min), systemic vascular resistance (dynes · s Ϫ1 · cm Ϫ5 ), central venous and pulmonary artery occlusion pressure (mm Hg), and troponin I (ng/mL). After the induction of anesthesia and at admission to the ICU, left ventricular systolic function and afterload were assessed by transesophageal echocardiography by using standard measurements and formulas: fractional shortening (%), fractional area change (%), global left ventricular wall motion, and left ventricular end-systolic wall stress (dynes/ cm 2 ) (21,22). The preoperative morbidity of patients was determined by the modified Cleveland score (23).…”
Section: Methodsmentioning
confidence: 99%
“…Decrease in systemic blood pressure after bolus injection of propofol is dependent on both vasodilation with reduced preload and after load and myocardial depression (negative inotropic action). 4 Wu et al 5 also concluded that etomidate preserve hemodynamic stability during anesthesia. Larsen et al 6 examined the effects of propofol upon myocardial function by measuring changes in left ventricle function using transthoracic tissue-Doppler echocardiography and concluded that a decrease in MAP with propofol is secondary to reduce cardiac filling or a consequence of a direct negative inotropic action of propofol.…”
Section: Discussionmentioning
confidence: 98%